Evaluation of Concrete Durability Performance with Sodium Silicate Impregnants. (20th August 2014) - Park, Sang-Soon; Kim, Yun Yong; Lee, Byung Jae; Kwon, Seung-Jun
Abstract : This paper presents an enhanced performance in concrete impregnated with silicate compound. Two different types of impregnant materials (inorganic and combined type) are applied to concrete samples with different strength grade (21 MPa and 34 MPa). Through lab-scale test, improved performances in impregnated concrete are evaluated regarding porosity, strength, chloride diffusion coefficient, permeability of air/water, and absorption. Long-term exposure tests including strength, chloride penetration depth and contents, and electrical potential for steel corrosion are performed for different marine conditions. While the surface-impregnated concrete shows marginal increase in strength, significant improvements of porosity, absorption, and permeability are evaluated. The resistance to chloride attack reasonably improved through simply spraying the inorganic silicate in atmospheric-salt spraying condition.